A unique error signature for human DNA polymerase ν - Arana, Mercedes E. (2006)
Human DNA polymerase ν is one of three A family polymerases conserved in vertebrates. Although its biological functions are unknown, pol ν has been implicated in DNA repair and in translesion DNA synthesis (TLS). Pol ν lacks intrinsic exonucleolytic proofreading activity and discriminates poorly against misinsertion of dNTP opposite template thymine or guanine, implying that it should copy DNA with low base substitution fidelity. To test this prediction and to comprehensively examine pol ν DNA synthesis fidelity as a clue to its function, here we describe human pol ν error rates for all 12 single base-base mismatches and for insertion and deletion errors during synthesis to copy the lacZ α-complementation sequence in M13mp2 DNA. Pol ν copies this DNA with average single-base insertion and deletion error rates of 7 × 10(−5) and 16 × 10(−5), respectively. This accuracy is comparable to that of replicative polymerases in the B family, lower than that of its A family homolog, human pol γ, and much higher than that of Y family TLS polymerases. In contrast, the average single base substitution error rate of human pol ν is 3.5 × 10(−3), which is inaccurate compared to the replicative polymerases and comparable to Y family polymerases. Interestingly, the vast majority of errors made by pol ν reflect stable misincorporation of dTMP opposite template G, at average rates that are much higher than for homologous A family members. This pol ν error is especially prevalent in sequence contexts wherein the template G is preceded by a C-G or G-C base pair, where error rates can exceed 10%. Amino acid sequence alignments based on the structures of more accurate A family polymerases suggest substantial differences in the O-helix of pol ν that could contribute to this unique error signature.